As certificações de sustentabilidade construtiva LEED e AQUA-HQE e a agregação de valor nos processos produtivos, comerciais e operacionais de edifícios comerciais no Brasil - Cristiane Silveira de Lacerda (2015)
This dissertation aims to present the topic of sustainability in construction and the adding value investigation in commercial buildings through the acquisition of sustainable construction certifications LEED (Leadership in Energy and Environmental Design) from USGBC - United States Green Building Council and AQUA-HQE (High Environmental Quality or Haute Qualité Environnmentale) from Fundação Vanzolini. At first, it presents the literature review that contemplates the subjects in reference, starting with a more open view to a more specific: the concepts of sustainable development, the concepts of sustainable construction, sustainable construction certificates existing in Brazil, the LEED certification, the AQUA-HQE certification, the value engineering and discussions of corporate sustainability. The dissertation methodology examines the two main sustainable construction certifications existing in Brazil on the typology of commercial buildings, the LEED certification and the AQUA-HQE certification. And in order to better understand the scenery of value creation, this research presents the results of a questionnaire with 94 questions responded by professionals from construction companies or investors companies that realized the certification process from the beginning to the end. The questions aimed to cover the targeted of value creation factors in three different stages of the certificated commercial building life cycle: during building construction, at the marketing stage and in phase of operation and maintenance. In order to realize the present research, the structured sample from market to identify and select the entrepreneurs, investors and constructors that realized commercial buildings and received the LEED or AQUA-HQE certification was a determinant factor. In conclusion, the text is about the value creation perceptions of professionals selected respondents, companys executives, those that already obtained certification for its commercial buildings, and that answered the questionnaire expressing their experience.